Incremental Social Innovation from a Historical Perspective - Dr. Nabegha Mahmood,; Rabia Aamir, (Al-Qanṭara, 2023)
Understanding the role of incremental social innovation with its key manifestations- mental models and enactment strategies, this paper foregrounds the importance of social innovation for contemporary times. Social innovation is a phenomenon that either brings a radical or incremental conversion in society by enabling it to accomplish its objectives and preserving its existence in the bigger, global perspective. This shift is often backed by mental models which guide the social innovator in achieving such change and implementation strategies that reform society. Using a case study approach and deriving supporting evidence from historical records, this study reinforces and builds upon contemporary research done on this topic to explore mental models and implementation tactics of a radical social innovator and an incremental social innovator in a historical leadership scenario. The findings of this study have extracted several pieces of evidence from historical archives for incremental social innovation witnessed and experienced by Islamic society led by the second Rashidun caliph Hazrat Umar. These results support the findings of global research in the field. Keywords: Social Innovation, Incremental social innovation/innovator, mental models, implementation tactics.